Brain insulin action: Implications for the treatment of schizophrenia. (15th May 2020) - Agarwal, Sri Mahavir; Kowalchuk, Chantel; Castellani, Laura; Costa-Dookhan, Kenya A.; Caravaggio, Fernando; Asgariroozbehani, Roshanak; Chintoh, Araba; Graff-Guerrero, Ariel; Hahn, Margaret
Abstract: Insulin action in the central nervous system is a major regulator of energy balance and cognitive processes. The development of central insulin resistance is associated with alterations in dopaminergic reward systems and homeostatic signals affecting food intake, glucose metabolism, body weight and cognitive performance. Emerging evidence has highlighted a role for antipsychotics (APs) to modulate central insulin-mediated pathways. Although APs remain the cornerstone treatment for schizophrenia they are associated with severe metabolic complications and fail to address premorbid cognitive deficits, which characterize the disorder of schizophrenia. In this review, we first explore how the hypothesized association between schizophrenia and CNS insulin dysregulation aligns with the use of APs. We then investigate the proposed relationship between CNS insulin action and AP-mediated effects on metabolic homeostasis, and different domains of psychopathology, including cognition. We briefly discuss a potential role of CNS insulin signaling to explain the hypothesized, but somewhat controversial association between therapeutic efficacy and metabolic side effects of APs. Finally, we propose how this knowledge might inform novel treatment strategies to target difficult to treat domains of schizophrenia. This article is part of the issue entitled 'Special Issue on Antipsychotics'. Highlights: Antipsychotic medications may alter central insulin signalling pathways, contributing to disruptions in whole body glucose and feeding homeostasis. Central insulin resistance may also interact with schizophrenia pathophysiology. Understanding these interactions further may lead to new intervention strategies. Future directions and treatments targeting central insulin resistance in schizophrenia are suggested.